RNA-guided genome engineering: paradigm shift towards transposons - Chang, Chin-Wei; Truong, Vy Anh; Pham, Nam Ngoc; Hu, Yu-Chen (Trends in biotechnology (Regular ed.), 2024)
CRISPR-associated transposon (CAST) and obligate mobile element guided activity (OMEGA) systems derived from transposons are burgeoning RNA-guided genome engineering tools.CASTs are promising RNA-guided, double-strand break-free tools to engineer prokaryotes that are difficult to edit using conventional CRISPR systems.CASTs can be used for bacterial metabolic engineering and targeted DNA insertion into microorganisms in a complex community.The prokaryotic TnpB and eukaryotic Fanzor proteins in the OMEGA system are promising hypercompact RNA-guided nucleases for eukaryotic genome editing. CRISPR-Cas systems revolutionized the genome engineering field but need to induce double-strand breaks (DSBs) and may be difficult to deliver due to their large protein size. Tn7-like transposons such as CRISPR-associated transposons (CASTs) can be repurposed for RNA-guided DSB-free integration, and obligate mobile element guided activity (OMEGA) proteins of the IS200/IS605 transposon family have been developed as hypercompact RNA-guided genome editing tools. CASTs and OMEGA are exciting, innovative genome engineering tools that can improve the precision and efficiency of editing. This review explores the recent developments and uses of CASTs and OMEGA in genome editing across prokaryotic and eukaryotic cells. The pros and cons of these transposon-based systems are deliberated in comparison to other CRISPR systems. CRISPR-Cas systems revolutionized the genome engineering field but need to induce double-strand breaks (DSBs) and may be difficult to deliver due to their large protein size. Tn7-like transposons such as CRISPR-associated transposons (CASTs) can be repurposed for RNA-guided DSB-free integration, and obligate mobile element guided activity (OMEGA) proteins of the IS200/IS605 transposon family have been developed as hypercompact RNA-guided genome editing tools. CASTs and OMEGA are exciting, innovative genome engineering tools that can improve the precision and efficiency of editing. This review explores the recent developments and uses of CASTs and OMEGA in genome editing across prokaryotic and eukaryotic cells. The pros and cons of these transposon-based systems are deliberated in comparison to other CRISPR systems.